Technoeconomic study of hightemperature acid sludge processing in molten medium - Гликин, Марат Аронович; Шовкопляс, Юлия Александровна; Тарасов, Вадим Юрьевич (Eastern-European Journal of Enterprise Technologies, 2014)
Throughout theterritoryofUkraine2 million tons of hazardous wastes are accumulated in outdoor areas. Recently, the determination to solve the problem of waste management is increased. Acid sludges are wastes of hazard class 2, containing free sulfuric acid (up to 70%) and organic part (mostly high-molecular aromatic compounds), which complicate the effective disposal. The problem state of acid sludges is considered and the main directions in their processing are defined. The combination of systems with a high-temperature coolant and aerosol nanocatalysis on an autonomous mobile unit, allowing to dispose acid sludges not less than 99.99 % is first considered. A basic energotechnological scheme including stages of preparation, high-temperature oxidation in sodium chloride melt and catalytic flue gas final purification in the aerosol reactor with obtaining electricity and sulphates, is proposed. The technicoeconomic analysis showed that the pay-back period of capital investment could reach 2 years. The obtained results will resolve the problem of half a million tons of acid sludges inUkraine.